2005
DOI: 10.1111/j.1440-1789.2004.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Chondromyxoid fibroma of the parietal bone

Abstract: We report the case of an 11-year old girl who presented with an intracranial chondromyxoid fibroma arising from parietal bone. Chondromyxoid fibroma is a benign cartilaginous neoplasm, which can be easily mistaken for chondrosarcoma, especially in small biopsies. It is more common in long bones and is least common in cranial bones. Published work describes about 33 cases occurring in cranial bones with almost equal incidence in the bones of the base of the skull and cranial vault. To our knowledge, this is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Some authors have described a female predisposition for intracranial tumors [16, 17]. In the series of 33 cases reported by Karkuzhali et al [18], the most common site was in the frontal bones, followed by the sphenoid bone, occipital bones, temporal bones and clivus. The patients were predominantly in their fifth decade of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have described a female predisposition for intracranial tumors [16, 17]. In the series of 33 cases reported by Karkuzhali et al [18], the most common site was in the frontal bones, followed by the sphenoid bone, occipital bones, temporal bones and clivus. The patients were predominantly in their fifth decade of life.…”
Section: Discussionmentioning
confidence: 99%
“…Calcifications may be noted either radiographically—in 3–16% of cases [3, 20]—or microscopically—in 7–27% of cases [3, 18, 20, 21]. Yamaguchi and Dorfman [22] have reported that patients with calcifications tend to be older (mean age 46 years) than those without calcifications (21 years), and that calcifications are associated with a longer duration of symptoms (43.2 months) compared to tumors without calcification (6.4 months).…”
Section: Discussionmentioning
confidence: 99%
“…Karkuzhali ature, none of which were in the sellar region. 9 Location in the ethmoid, mastoid, clivus, temporal, occipital and spheno-occipital bones has been described. The symptoms of CMF include discomfort and pain accompanied by local swelling depending on the site and size of the tumor.…”
Section: Discussionmentioning
confidence: 98%
“…The CT scan shows osteolytic lesions with a sclerotic margin. 9 The tumor may show foci of calcification, with mineralization that is observed radiologically in about 13% of patients. 12 A low-to-intermediate signal intensity is observed on T1-weighted MRI and hyperintensity that indicates water content on T2-weighted MRI.…”
Section: Discussionmentioning
confidence: 99%
“…1 It also frequently affects flat bones. 5,6 Its typical radiographic finding manifests as a well-circumscribed, eccentric, osteolytic lesion with a sclerotic rim. 1 Histologically, chondromyxoid fibromas show stellate or spindle-shaped cells dispersed in the myxochondroid matrix, which has increased cellularity in the periphery dividing the matrix into pseudolobules.…”
Section: Discussionmentioning
confidence: 99%